Features of the Development of Physical Qualities of Young Football Players at the Stage of Initial Training (Texas Journal of Multidisciplinary Studies, 2022)
Based on the monitoring analysis of development-related physical qualities, the article outlines an accentuated methodology aimed at educating the necessary motor qualities in young football players. A staged methodology of sports specialization has been developed and experimentally tested, and its effective ways of development have been determined.